2022
DOI: 10.7759/cureus.31150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Therapy on Mortality and Recurrence of Intracerebral Hemorrhage in Patients With Spontaneous Intracerebral Hemorrhage

Abstract: Statins can play an essential role in the tertiary and primary prevention of cardiovascular events by reduction of cholesterol in a stroke patient. This meta-analysis aims to assess statin therapy's effect on mortality and recurrence of Intracranial Hemorrhage (ICH) in patients with spontaneous ICH. The current meta-analysis was conducted following Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA) guidelines. A systematic search was performed using PubMed, EMBASE, and Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, statins can reduce the risk of recurrent intracerebral haemorrhage (ICH) in patients of spontaneous ICH. 6 Thus, we need not withhold or reduce the dose of statin in apprehension of ICH. However, further research is needed in this special group of population as in a Chakraborty / IP Indian Journal of Neurosciences 2024;10(1):49-50 recent meta-analysis it was found that there was an evidence for a small increased risk of haemorrhagic stroke events with LDL-C-lowering therapies though no clear evidence was noted with triglyceride-lowering therapies.…”
mentioning
confidence: 99%
“…On the contrary, statins can reduce the risk of recurrent intracerebral haemorrhage (ICH) in patients of spontaneous ICH. 6 Thus, we need not withhold or reduce the dose of statin in apprehension of ICH. However, further research is needed in this special group of population as in a Chakraborty / IP Indian Journal of Neurosciences 2024;10(1):49-50 recent meta-analysis it was found that there was an evidence for a small increased risk of haemorrhagic stroke events with LDL-C-lowering therapies though no clear evidence was noted with triglyceride-lowering therapies.…”
mentioning
confidence: 99%